Integrated X-ray crystallography, optical and computational methods in studies of structure and luminescence of new synthesized complexes of lanthanides with ligands derived from 2,6-diformylpyridine - De Oliveira, Gelson Manzoni; MacHado, Aline; Gomes, Geraldo Wachholz; Monteiro, Jorge H.S.K. [UNESP]; Davolos, Marian R. [UNESP]; Abram, Ulrich; Jagst, Alexander (Elsevier, 2011)
The reaction of 2,6-diformylpyridine-bis(benzoylhydrazone) [dfpbbh] and 2,6-diformylpyridine-bis(4-phenylsemicarbazone) [dfpbpsc] with lanthanides salts yielded the new chelates complexes [Eu(dfpbpsc-H +) 2]NO 3 (1), [Dy(fbhmp) 2][Dy(dfpbbh-2H +) 2]·2EtOH·2H 2O (fbhmp = 2-formylbenzoylhydrazone-6-methoxide-pyridine; Ph = phenyl; Py = pyridine; Et = ethyl) and [Er 2(dfpbbh-2H +) 2(μ-NO 3)(H 2O) 2(OH)]·H 2O. X-ray diffraction analysis was employed for the structural characterization of the three chelate complexes. In the case of complex 1, optical, synthetic and computational methods were also exploited for ground state structure determinations and triplet energy level of the ligand and HOMO-LUMO calculations, as well as for a detailed study of its luminescence properties. © 2010 Elsevier Ltd. All rights reserved.
Keywords: Europium(III) luminescent complexes; Lanthanides chelate complexes; Luminescence